Is basal serum 17-OH progesterone a reliable parameter to predict nonclassical congenital adrenal hyperplasia in premature adrenarche? - Gönç, E. Nazlı; Özön, Z. Alev; Alikaşifoğlu, Ayfer; Engiz, Özlem; Bulum, Burcu; Kandemir, Nurgün (The Turkish Journal of Pediatrics, 2011)
To determine the critical features for the diagnosis of nonclassical 21 hydroxylase deficiency (NC210HD) without performing adrenocorticotropic hormone (ACTH) test, we studied 186 cases with premature adrenarche. Clinical and laboratory features as well as basal 17-hydroxyprogesterone (17-OHP) were analyzed to determine factors important for differentiating NC21OHD. Overall, 6 patients (3.2%) had ACTH-stimulated 17-OHP > 10 ng/ml. A cutoff level of 2 ng/ml for basal 17-OHP was 66.7% sensitive and 78% specific for NC21OHD; however, a cutoff level of 1.55 ng/ml had higher sensitivity (83%) and specificity (70.6%). A cutoff of 1.55 ng/ml would lead to 31% of cases with premature adrenarche having to undergo ACTH test, and only one case would have been missed. That case had a bone age SDS > 2. Three cases out of five with a basal 17-OHP > 5 ng/ml had stimulated 17-OHP < 10 ng/ml. A cutoff of 1.55 ng/ml for basal 17-OHP together with bone SDS > 2 in those with lower basal levels as a guide for carrying out an ACTH test may yield better results in the diagnosis of NC21OHD in the premature adrenarche population. A cutoff of 5 ng/ml for basal 17-OHP should not be used for diagnosis of NC21OHD.